La evolución regresiva de la vegetación en la cuenca de Quillota, curso medio río Aconcagua - Quintanilla P., V. Guillermo (Investigaciones Geográficas: Una mirada desde el sur, 1977)
The antrophic action upon the landscape of the mid valley of the Aconcagua river in Central Chille, dates from the pre-incasic period (to the end of 14 th. century. Due to the mildness of the weather, the fertility of the soil, the great contribution of the hydric resources, the road net connected with the main economical centers of the country end, because of the geographic-administradive importance that Chile always had in this zone, the deep valley of Quillota has experimented, apoximatly a rational and diversified explotation of its renewable natural resources through its history. For that reason the natural vegetation of the region (the formation of sclerophile forest and shrub by steppe) has not suffered in these six centuries, a considerable retrocession neither a hard colonization impact of foreign plants. The felling of trees searching terrains fw tho cultivation and cattle the necessity of the habitat building and combustible, the mining acticities have been the plincipal factors responsable of the reduction of the vegetal biomass generating mining erosive process on some mountains. That is why conclued that the autochthomous vegetation of this deep valley has not suffered a great dissapearence of native species, it has suffered a regression in its geogaphic areas of dispersion (or growing) and a lost of its density such as closed primitive formations that today constitute semi closed or open communities such as the case of the steppe formation of the Acacia caven.